The Art of Radio Documentary - Grenersen, Geir (Proceedings from the Document Academy, 2017)
The two Sámi brothers Hans and Eilert Karlsen were the last remaining inhabitants of a vacated fishing hamlet on the arctic coast of Finnmark. In 1992, a Norwegian journalist made a radio documentary about the brothers. I recorded this documentary on my cassette player, and since the documentary is no longer available online, I have based my reflections on my old recordings. Both the recording technology and the brothers’ way of living is history now.